2016
DOI: 10.1037/dev0000128
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawing to a virtual world: Associations between subtypes of withdrawal, media use, and maladjustment in emerging adults.

Abstract: An approach-avoidance model of social withdrawal (Asendorpf, 1990) identifies 3 types of social withdrawal including shyness, unsociability, and avoidance. Each appears to be uniquely associated with varying indicators of maladjustment in emerging adulthood (Nelson, 2013) but little, if any, work has been done to see how they might be linked to media use in the third decade of life. Therefore, the purpose of this study was to examine longitudinally the links between subtypes of social withdrawal, connective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 40 publications
5
40
1
Order By: Relevance
“…To date, there has been very limited empirical comparison of the cognitive, social, and emotional correlates of subtypes of social withdrawal in emerging adulthood (Bowker et al, 2017;Barry et al, 2013;Nelson, 2013;Nelson et al, 2016). Drawing upon developmental, clinical, and cognitive perspectives, Study 1 was the first to explore the potential different patterns of associations between subtypes of social withdrawal (shyness, unsociability, social avoidance), maladaptive cognitions (threatening, negative), and internalizing problems (social anxiety, depressive symptoms) in a sample of emerging adults.…”
Section: Discussion -Studymentioning
confidence: 99%
See 4 more Smart Citations
“…To date, there has been very limited empirical comparison of the cognitive, social, and emotional correlates of subtypes of social withdrawal in emerging adulthood (Bowker et al, 2017;Barry et al, 2013;Nelson, 2013;Nelson et al, 2016). Drawing upon developmental, clinical, and cognitive perspectives, Study 1 was the first to explore the potential different patterns of associations between subtypes of social withdrawal (shyness, unsociability, social avoidance), maladaptive cognitions (threatening, negative), and internalizing problems (social anxiety, depressive symptoms) in a sample of emerging adults.…”
Section: Discussion -Studymentioning
confidence: 99%
“…Moreover, extreme group comparisons indicated that unsociable youth reported higher levels of depression (that did not differ from shy and socially avoidant peers) than comparison non-withdrawn emerging adults. In contrast, Nelson et al (2016) reported that correlation analyses examining the associations between unsociability and depression assessed at two timepoints yielded mixed findings, including significant positive associations as well as non-significant negative associations. Thus, although the extant literature suggests that unsociability poses less risk for socio-emotional maladjustment as compared to shyness and social avoidance, additional empirical exploration of unsociability across developmental periods is needed.…”
Section: Unsociabilitymentioning
confidence: 97%
See 3 more Smart Citations